Bilateral brachymetatarsia : a rare case report - Norliyana M,; Mohd Yazid Bajuri,; Abdul Muhaimin A, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Brachymetatarsia is a conditioned which has been described as abnormal short metatarsal bone due to premature closure of the epiphyseal growth plate. It usually involves a single metatarsal bone with the fourth metatarsal being the most common. It may be congenital or acquired. We here report a case in a 53-yearold lady who presented with foot pain and shoe wearing problem. Examination revealed shortening of the bilateral fourth toe and the toes were tilted dorsally. She was diagnosed with bilateral brachymetatarsia and operation was done mainly for cosmetic reasons. Gradual lengthening with distraction osteogenesis was performed using a MiniRail external fixator (Orthofix) and K-wiring of the right fourth metatarsophalangeal joint. Adequate length of fourth metatarsal and good bony union were achieved at the end of treatment.